The Inheritance Rights Of Children From Sperm Donor In A Review Of Health Law N0.17 Of 2023 And Fiqh Of Imam Syafi'i - Edwardsyah Bernardkent; Sunan Autad Sarjana; Fadhila Tianti Mudi Awalia,; Usamah Abdurrahman (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The development of assisted reproductive technology, particularly sperm donation, raises legal issues regarding the validity of lineage and inheritance rights of children. Under Indonesian law, Law No. 17 of 2023 concerning Health restricts assisted reproductive technology to legally married couples, based on medical indications, and not in conflict with religious norms.This study aims to analyze the compatibility of the provisions on third-party sperm donors in Law Number 17 of 2023 with the concept of lineage in the Shafi'i school of thought. This study also aims to examine the status and inheritance rights of children born from sperm donors according to the Shafi'i school of thought and Indonesian positive law.The method used is normative legal research with a normative-comparative approach through analysis of primary, secondary, and tertiary legal materials. The study was conducted on Law Number 17 of 2023, the Compilation of Islamic Law, the Civil Code, and customary law.The results of this study indicate that third-party sperm donation is not permitted under both Indonesian positive law and the Shafi'i school of thought because it contradicts the validity of marriage and the protection of lineage. Children born from sperm donation do not have a lineage relationship and inheritance rights to the donor. However, the legal relationship and inheritance rights to the mother are still recognized as long as they comply with applicable legal provisions. The gap in this research is the lack of studies that simultaneously link health regulations, Shafi'i fiqh, and inheritance law. The novelty of this research lies in the comparative formulation that emphasizes the consistency of lineage protection as the basis for determining a child's legal status and inheritance rights.